2002
DOI: 10.1590/s0100-72032002000800005
|View full text |Cite
|
Sign up to set email alerts
|

Análise Comparativa de Testes Diagnósticos para Diabete Gestacional

Abstract: RESUMOObjetivos: avaliar os resultados maternos e perinatais de pacientes submetidas à curva glicêmica com 100 g de glicose, de acordo com três diferentes critérios diagnósticos. Métodos: realizou-se estudo do tipo corte transversal, incluindo 210 pacientes assistidas no Instituto Materno-Infantil de Pernambuco (IMIP), submetidas durante a gravidez ao teste oral de tolerância à glicose 100 g (TOTG), com gestação única, sem história de diabete ou intolerância aos carboidratos prévia à gestação e cujo parto foi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The episiotomy was introduced as routine in these deliveries, although in the absence of consistent scientific indications of its efficacy (5) ,with the intention of preventing cerebral hemorrhages and reducing perinatal asphyxia. Nevertheless, as per a systematic review, there are no data that support the assertion that the liberal use of episiotomy minimizes fetal head trauma (25,26) . At the Normal Delivery Center [CPN] of HGIS, selective episiotomy is recommended, and normal deliveries are assisted by obstetric nurses who, if necessary, request medical evaluation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The episiotomy was introduced as routine in these deliveries, although in the absence of consistent scientific indications of its efficacy (5) ,with the intention of preventing cerebral hemorrhages and reducing perinatal asphyxia. Nevertheless, as per a systematic review, there are no data that support the assertion that the liberal use of episiotomy minimizes fetal head trauma (25,26) . At the Normal Delivery Center [CPN] of HGIS, selective episiotomy is recommended, and normal deliveries are assisted by obstetric nurses who, if necessary, request medical evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…In a study on elective prematurity (2) , a 94.4% rate of C-sections was identified. Other studies on prematurity or diseases during gestation that result in prematurity report that the high rates of C-sections (51.2%, 52.5%, and 56%) are justified by the high-risk population (18,25) . In the present study, the rate of cesarean sections was shown to be well below these values.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, there is one methodological limitation that should be highlighted, which is that this was a retrospective study in which 532 cases were excluded. According to an earlier study carried out at our center using the same methodology, approximately 40% of cases were not included because of missing hospital records 29 . The importance of these exclusions is that the sensitivity and specificity calculations, while similar to the literature, may be under or overestimated.…”
Section: Resultsmentioning
confidence: 99%
“…It is vitally important to carry out glycemic control to improve the prognosis as early as possible, due to the deleterious effects of hyperglycemia on the pregnant woman and that consequently reaches the fetus through facilitated diffusion, generating an exaggerated production of insulin, which can cause several problems in relation to the fetus such as macrosomia, hypoglycemia, fetuses large for gestational age, intrauterine fetal death, among others. Since prenatal care must be followed, it is essential that each health service adopt a unique standard of diagnosis 9,13 .…”
Section: Source: State Health Department 20mentioning
confidence: 99%